Semi-Empirical Predictions on the Structure and Properties of ent-Kaurenoic Acid and Derivatives - Jose Isagani B. Janairo; Gerardo C. Janairo; Derrick Ethelbhert C. YU (E-Journal of Chemistry)
The physicochemical properties of ent- kaurenoic acid model derivatives, which possibly influence its therapeutic application, were calculated. Results revealed that the molecule possess favourable attributes which renders it possible to be considered as a drug lead only that its very hydrophobic nature can result to poor bioavailabilty, low absorption and poor systemic circulation. In silico simulations revealed that this setback can be overcome by introduction of hydroxyl group to the tertiary carbon of ent-kaurenoic acid employing m-CPBA catalyzed hydroxylation, thus, unleashing its full drug potency. Moreover, molecular similarity analyses derived from semi-empirical calculations between ent-kaurenoic acid and a set of kaurane diterpenoids showed differences in hydrophobic complementarity, size and electronic properties despite possessing nearly identical molecular frameworks, thus, arriving in a generalization for their observed mechanistic differences on acting on different targets.